PENGARUH MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION DAN TIPE JIGSAW TERHADAP PRESTASI DAN MOTIVASI BELAJAR SISWA SMP - Asnawi Asnawi; M. Ikhsan; Hajidin Hajidin (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2020)
Innovative and fun learning models place students at the center of learning including the STAD type cooperative learning model and the Jigsaw type cooperative learning model. Learning using the cooperative model type STAD and Jigsaw is considered capable of improving student achievement through group discussion and investigation through various sources used by students. The purpose of this study was to determine differences in learning achievement between students who were taught with the Jigsaw Type Cooperative Learning Model and students who were taught with the STAD Type Cooperative Learning Model on Statistics material. This research is an experimental research design with a Pretest-Posttest Control Design Group. The population in this study were all eighth grade students of SMP Negeri 1 Trienggadeng even semester 2016/2017 academic year. While the sample is a portion of the population taken using the Random Sampling technique taken by 2 classes, namely Class VIII-3 and Class VIII-5. Class VIII-3 for the Jigsaw learning model and Class VIII-5 for the STAD learning model. The instrument used to obtain research data in the form of student achievement tests and student motivation questionnaires. The statistical test used to analyze data on differences in learning achievement and student motivation questionnaires is the t-test. The results showed that there were differences in learning achievement and motivation between students who were taught with the Jigsaw type cooperative learning model and students who were taught with the STAD type cooperative learning model. Abstrak Model pembelajaran yang inovatif dan menyenangkan menempatkan siswa sebagai pusat belajar diantaranya adalah model pembelajaran kooperatif tipe STAD dan model pembelajaran kooperatif tipe Jigsaw. Pembelajaran menggunakan model kooperatif tipe STAD dan Jigsaw dinilai mampu meningkatkan prestasi belajar siswa melalui diskusi kelompok dan investigasi melalui berbagai sumber yang digunakan siswa. Tujuan penelitian ini untuk mengetahui perbedaan prestasi belajar antara siswa yang diajar dengan Model Pembelajaran Kooperatif Tipe Jigsaw dan siswa yang diajarkan dengan Model Pembelajaran Kooperatif Tipe STAD pada materi Statistik. Penelitian ini merupakan penelitian eksperimen dengan desain penelitian Pretest-Posttest Control Grup Desain. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 1 Trienggadeng semester genap tahun pelajaran 2016/2017. Sedangkan sampelnya adalah sebagian dari populasi yang diambil dengan menggunakan teknik Random Sampling yang diambil 2 kelas yaitu Kelas VIII-3 dan Kelas VIII-5. Kelas VIII-3 untuk model pembelajaran Jigsaw dan kelas VIII-5 untuk model pembelajaran STAD. Instrumen yang digunakan untuk memperoleh data penelitian berupa tes prestasi belajar dan angket motivasi siswa. Uji statistik yang digunakan untuk mengalisis data perbedaan prestasi belajar dan angket motivasi siswa adalah Uji-t. Hasil penelitian menunjukkan bahwa terdapat perbedaan prestasi belajar dan motivasi antara siswa yang diajar dengan model pembelajaran kooperatif tipe Jigsaw dan siswa yang diajar dengan model pembelajaran kooperatif tipe STAD. Kata Kunci: Pembelajaran Jigsaw, Pembelajaran STAD, Prestasi Belajar, Motivasi